2022
DOI: 10.3389/fendo.2022.1000185
|View full text |Cite
|
Sign up to set email alerts
|

Association of GLP1R variants rs2268641 and rs6923761 with obesity and other metabolic parameters in a Polish cohort

Abstract: IntroductionObesity is a complex disease associated with excessive fat accumulation and numerous metabolic complications. So far, many factors leading to the development of this disorder have been identified, including genetic susceptibility. Various studies linked GLP1R variants with anthropometric and metabolic parameters, suggesting the role of the variation in this gene in metabolic health.ObjectiveThe aim of this study is to investigate the association of two single nucleotide variants of GLP1R gene, rs22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Variants rs2268641 and rs6923761 in this gene correlate with a high BMI [ 102 , 103 ]. Carriers of the AA genotype of rs6923761 have a higher risk of obesity and higher glucose levels [ 104 ]. Variant rs10305492 in a European population [ 105 ] and rs3765467 and rs10305492 in a Chinese population [ 106 ] have been implicated in metabolic syndrome and a higher risk of T2DM.…”
Section: Resultsmentioning
confidence: 99%
“…Variants rs2268641 and rs6923761 in this gene correlate with a high BMI [ 102 , 103 ]. Carriers of the AA genotype of rs6923761 have a higher risk of obesity and higher glucose levels [ 104 ]. Variant rs10305492 in a European population [ 105 ] and rs3765467 and rs10305492 in a Chinese population [ 106 ] have been implicated in metabolic syndrome and a higher risk of T2DM.…”
Section: Resultsmentioning
confidence: 99%
“…In tailhead adipose tissue, GLP1R was upregulated in females. In addition to being associated with feed e ciency, this gene is also associated with obesity in humans [78], and GLP-1 analogues such as semaglutide are used for the treatment of obesity and diabetes [79]. These cattle do not eat industrially produced food.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, Michałowska et al revealed a tendency to hyperglycemia in carriers of the AA rs6923761 genotype, compared with carriers of the AG rs6923761 genotype, but found no association with the metabolic syndrome, which also coincided with the results of our studies. 48 Sathananthan et al 49 , also Daniel Antonio de Luis et al demonstrated that GLP-1R in heterozygotes for SNV rs6923761 of the GLP1R gene (GA genotype) has a low receptor affinity for GLP-1, which leads to relatively reduced insulin secretion in response to GLP-1 infusion and, as a result, promotes the development of hyperglycemia. Individuals with the A allele of SNV rs6923761 of the GLP1R gene and morbid obesity have higher levels of triglycerides, insulin, and insulin resistance.…”
Section: Discussionmentioning
confidence: 99%